Business plan Expansion of Whittard of Chelsea franchise - Nešporová, Tereza (2014)
The objective of this diploma thesis is to propose expansion possibilities for Whittard of Chelsea franchise on the Czech market through opening British style cafes. The thesis analyses the situation in South-Moravian region, namely in Brno, Vyskov and Slavkov u Brna cities. The thesis is divided into two key parts. The initial part, theoretical research, mainly describes the structure of business plan and business model, followed by the explanation of financial and market analyses, and market research theory. Own work focuses on developing essential parts of business plan for the Whittard of Chelsea café, based also on the competitors' analysis and conducted costumer survey. The conclusion proposes the expansion opportunity and its vital conditions for this development in South-Moravian region.